Aplikasi Sistem Pakar Diagnosa Penyakit Anjing Berbasis Facebook Messenger - Flores, Veronica Ambassador; Linawati, Linawati (Majalah Ilmiah Teknologi Elektro, 2020)
Abstract—An Expert System of Disease Diagnosis in Dogs Based on Facebook Messenger was a useful application to provide an initial diagnosis of the diseases based on the symptoms given by the users. The application uses the Facebook Messenger-based on Natural Language Processing (NLP) method to allow users to easily and comfortably interacting with the app. Diagnosis was obtained by identifying the pattern, and classifying the pattern. The method used in the pattern identification process is N-gram, this method was a matching pattern method where the number of words or character pattern that would be match could be adjusted. The method used to classify a disease is a Matching Template, this method worked by matching the template pattern with the test pattern to find the similarities between the patterns. The study concluded that the application of an expert systems using the N-gram method and the Matching Template had an accurate diagnosis rate of 80%.